Hypocholesterolemic potentials of garlic on the lipid profile of poultry birds and poultry products: A review - B. Adjei-Mensah; O. Oso; E. Oke; T.T. Kuka; P. Sasu; R.K. Agbehadzi; C.C. Atuahene; A. Donkoh; J.A. Hamidu; K. Tona (Journal of Applied Poultry Research)
Summary: The quality of meat and eggs, as well as consumer acceptance, is influenced by microbial load, flavor, and lipid oxidation. Recently, consumer preferences have shifted toward naturally healthy, disease-free poultry products that have no negative side effects. Natural additives are now gaining popularity in research due to the presence of microbial-resistant bacteria associated with synthetic products and feed additives. Garlic and its bioactive components (BCs) have been found to improve the quality of meat and egg yolks by affecting the activities of important enzymes such as squalene oxidase and HMG-CoA reductase, which are responsible for cholesterol and lipid synthesis. However, the extent to which the organosulphur compounds (OSCs) in garlic can enhance lipid stability and reduce total cholesterol depends on various variables including preparation technique, shelf life, rate of inclusion, and duration of supplementation in bird diets. Therefore, this review aims to highlight the impact of garlic supplementation on the lipid profiles and fatty acids in poultry.